Pragmatic trial on inhaled corticosteroid withdrawal in patients with COPD in general practice - van den Bemt, Lisette; van den Nieuwenhof, Lotte; Rutjes, Anne; van der Meer, Victor; Stege, Gerben; Wensing, Michel; Teichert, Martina; Schermer, Tjard (npj Primary care respiratory medicine, 2020)
The therapeutic value of inhaled corticosteroids (ICSs) for COPD is limited. In published RCTs, ICS could be withdrawn in COPD patients without increasing exacerbation risk when bronchodilator treatment is optimized. Here we report on the feasibility and risks of ICS withdrawal in Dutch general practice for COPD patients without an indication for ICSs. In our pragmatic trial, general practitioners decided autonomously which of their COPD patients on ICS treatment could stop this, how this was done, and whether additional bronchodilator therapy was needed. We recruited 62 COPD patients (58 analysed) who were eligible for ICS withdrawal in 79 practices. In 32 patients (55.2%, 95% CI: 42.5-67.3%) ICS was withdrawn successfully, 19 (32.8%, 95% CI: 22.1-45.6%) restarted ICS treatment within six months, 12 patients (20.7%, 95% CI: 12.3-32.8%) had a moderate exacerbation, and one patient had a severe exacerbation. ICS withdrawal was successful in just over half of the patients with COPD without an indication for ICS.